Bacteria Modify Their Sensitivity to Chemerin-Derived Peptides by Hindering Peptide Association With the Cell Surface and Peptide Oxidation - Godlewska, Urszula; Bilska, Bernadetta; Majewski, Paweł; Pyza, Elzbieta; Zabel, Brian A.; Cichy, Joanna (Frontiers in Microbiology, 2020)
Chronic inflammatory skin diseases like psoriasis alter the local skin microbiome and lead to complications such as persistent infection with opportunistic/pathogenic bacteria. Disease-associated changes in microbiota may be due to downregulation of epidermal antimicrobial proteins/peptides, such as antimicrobial protein chemerin. Here we show that chemerin and its bioactive derivatives have differential effects on the viability of different genera of cutaneous bacteria. The lethal effects of chemerin are enhanced by bacterial-derived ROS-induced chemerin peptide oxidation and suppressed by stationary phase sigma factor RpoS. Insight into the mechanisms underlying changes in the composition of cutaneous bacteria during autoreactive skin disease may provide novel ways to mobilize chemerin and its peptide derivatives for maximum antimicrobial efficacy.